Lipid metabolism in ferroptosis: mechanistic insights and therapeutic potential - Sun, Daoyun; Wang, Longfei; Wu, Yufan; Yu, Yi; Yao, Yufeng; Yang, Hongju; Hao, Chunlin (Frontiers in Immunology, 2025)
Ferroptosis, an iron-dependent form of regulated cell death driven by lipid peroxidation, plays a pivotal role in various physiological and pathological processes. In this review, we summarize the core mechanisms of ferroptosis, emphasizing its intricate connections to lipid metabolism, including fatty acid synthesis, phospholipid remodeling, and oxidation dynamics. We further highlight advancements in detection technologies, such as fluorescence imaging, lipidomics, and in vivo PET imaging, which have deepened our understanding of ferroptotic regulation. Additionally, we discuss the role of ferroptosis in human diseases, where it acts as a double-edged sword, contributing to cancer cell death while also driving ischemia-reperfusion injury and neurodegeneration. Finally, we explore therapeutic strategies aimed at either inducing or inhibiting ferroptosis, including iron chelation, antioxidant modulation, and lipid-targeted interventions. By integrating mechanistic insights, disease relevance, and therapeutic potential, this review provides a comprehensive perspective on ferroptosis as a crucial interface between lipid metabolism and oxidative stress.